Increasing Understanding of Fiqh: Problem Based Learning (PBL) Drives it All - Ananda Bunga Mutiara Dani Nasution; Elan Ilyas Sidiq; Muhamad Lufti Yasin Faujan; Imam Tabroni (International Journal of Integrative Sciences, 2023)
Jurisprudence learning at Madrasah Tsanawiyah requires learning methods and models that are diverse and in accordance with the subject matter taught by the teacher, by raising different problems in Jurisprudence learning. One learning model that can present various problems related to Islamic law and the development of issues that develop in people's lives is the Problem Based Learning learning model. This study uses a quantitative experimental research approach. With the experimental design of Pretest-Posttest Control Group Design or pre-experimental designs with the form of one-group pretest-posttest design. The student data obtained in this study are the results of learning Jurisprudence class VIII A MTsN 1 Purwakarta. The material used in this research is about the beauty of sharing with alms, grants, and gifts. (KKM) at the school is 75. The learning outcomes consist of pretest and posttest. It can be concluded that the Problem Based Learning (PBL) learning method has a positive effect on students' critical thinking skills